Representation of Poverty in the Novel Krikil Krikil Pasisir by Tamsir AS - Dinar Prabowo, Gilang; Supriyanto, Teguh (Program Studi Sastra Jawa, Fakultas Bahasa dan Seni, Universitas Negeri Semarang, 2025)
Poverty is a complex social phenomenon that affects various aspects of people's lives, including its representation in literary works. This study aims to describe the portrait of poverty in Tamsir AS's novel Krikil-Krikil Pasisir using a sociological approach. This approach views literary works as a reflection of the social structure and dynamics of the society within which they live. This study uses Ian Watt's sociological theory of literature using semiotic reading techniques. Primary data was obtained from the narrative text in the novel, while secondary data came from supporting scientific references. This reading method enters the data analysis stage, and interpreting the data requires an understanding of social and cultural literary codes. The results show that poverty is represented as a structural reality that influences thought patterns, behavior, and relationships between characters. The unequal social relations between coastal communities and certain dominant ethnic groups give rise to resistance and latent conflict. The characters in the novel experience moral dilemmas that demonstrate the complexity of human values within limited situations. Thus, this novel not only conveys individual stories but also speaks to the social crisis of Indonesia's marginalized communities.